2001
DOI: 10.1183/09031936.01.00093001
|View full text |Cite
|
Sign up to set email alerts
|

The effects of coronavirus on human nasal ciliated respiratory epithelium

Abstract: The effects of coronavirus on human nasal ciliated respiratory epithelium. M.A. Chilvers, M. McKean, A. Rutman, B.S. Myint, M. Silverman, C. O9Callaghan. #ERS Journals Ltd 2001. ABSTRACT: Human coronavirus (HCoV) accounts for 15-30% of common colds, but only one case report has described the effect of a coronavirus infection, that was asymptomatic, on human respiratory epithelium.The authors examined the effects of infection with HCoV on ciliary structure and function in healthy volunteers infected by intranas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(154 citation statements)
references
References 26 publications
4
148
0
2
Order By: Relevance
“…Viral infection can moreover cause a reduction of ciliary beat frequency, uncoordinated ciliary movement and a reduction in the number of ciliated cells (Chilvers et al, 2001;Smith et al, 2014a;Tristram et al, 1998). Given the importance of the mucociliary escalator for bacterial clearance, it is likely that reduced ciliary function hampers bacterial clearance from the LRT.…”
Section: Impairment Of Mucociliary Clearancementioning
confidence: 99%
“…Viral infection can moreover cause a reduction of ciliary beat frequency, uncoordinated ciliary movement and a reduction in the number of ciliated cells (Chilvers et al, 2001;Smith et al, 2014a;Tristram et al, 1998). Given the importance of the mucociliary escalator for bacterial clearance, it is likely that reduced ciliary function hampers bacterial clearance from the LRT.…”
Section: Impairment Of Mucociliary Clearancementioning
confidence: 99%
“…This was made possible by the recent advent of highresolution digital high-speed video imaging [18], which enabled us to assess the precise beat pattern of cilia by viewing the ciliary beat cycle frame by frame in different planes. Using this method, we have previously shown that cilia in certain conditions may have a normal beat frequency despite a markedly abnormal beat pattern [20], and normal ciliary beat frequency does not necessarily equate to normal ciliary function. Our finding of significantly reduced beat frequency and increased ciliary dyskinesia in the epithelium of native airway in the CF transplant recipients is in contrast to the study by READ et al [14] that showed a higher median (IQR) CBF of 10.8 (8.8-11.1) Hz in the native airway epithelium of the six adults with CF they studied.…”
Section: Discussionmentioning
confidence: 99%
“…Over a 2-yr period (2007)(2008)(2009) 20 children (aged ,18 yrs), who underwent flexible bronchoscopy following lung transplantation at the Great Ormond Street Hospital for Children (London, UK), were studied and demographic and clinical details were collected. All subjects underwent pH/impedance studies to examine for evidence of pathological gastro-oesophageal reflux.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, coronavirus replication can damage the respiratory epithelium and lead to bacterial superinfections. The human respiratory coronavirus 229E can disrupt the respiratory epithelium and cause ciliary dyskinesia [40]. Accordingly, virus-induced alterations of the respiratory epithelium would trigger the replication of other pathogens, causing respiratory diseases resembling the ITB complex.…”
Section: Canine Respiratory Coronavirusmentioning
confidence: 99%